2018
DOI: 10.31563/1684-7628-2018-46-2-117-129
|View full text |Cite
|
Sign up to set email alerts
|

Development of Resource-Saving Technology and Justification of Parameters of Machinery Complex for Agricultural Crops in the Urals Region

Abstract: РАЗРАБОТКА РЕСУРСОСБЕРЕГАЮЩЕЙ ТЕХНОЛОГИИ И ОБОСНОВАНИЕ ПАРАМЕТРОВ КОМПЛЕКСА МАШИН ДЛЯ ВОЗДЕЛЫВАНИЯ СЕЛЬСКОХОЗЯЙСТВЕННЫХ КУЛЬТУР В ЗОНЕ УРАЛАКлючевые слова: почвенно-климатические условия; свойства почвы; сельскохозяйственные культуры; технология; обработка почвы; посев; комплекс машин; металлоемкость; тяговое сопротивление; производительность; урожайность.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The recommended technology for tiling and sowing of crops envisages the application of the following types of working elements [4]:…”
Section: Advances In Engineering Research Volume 151mentioning
confidence: 99%
See 2 more Smart Citations
“…The recommended technology for tiling and sowing of crops envisages the application of the following types of working elements [4]:…”
Section: Advances In Engineering Research Volume 151mentioning
confidence: 99%
“…The calculations have demonstrated that farms with the ploughland area of 1000-1200 ha, crop rotation with sowing of various crops requires one tool for a tractor of draught class 3 with complete universalization, able to perform all types of primary and additional tilling and crop sowing using interchangeable working elements and modules. For average-sized farms with ploughland area of 7-10K ha, versatile tools are required for tractors of 3-5th draught class with interchangeable working elements for tilling (moldboard, non-moldboard, chisel), with interchangeable modules for tiling to the depth of 0.1-0.16 m and tilling and sowing machines with interchangeable modules for mulching, presowing tilling and sowing with different types of working elements to the depth of 0.06-0.1 m. Large agricultural holdings need single-operation combines for all technological operations performed by tractors of draught class 5-8 [4].…”
Section: Advances In Engineering Research Volume 151mentioning
confidence: 99%
See 1 more Smart Citation
“…Both agricultural science and practice have accumulated a great number of experimental factors that are taken into account in the design of new technological processes and working bodies [1,2,4,5,11,14] Constant improvement of technologies, agricultural machinery construction, intensification of modes of its work with simultaneous improvement of quality of performance of working processes complicate methods of calculation of structure and parameters of machines at their design. At the same time, methods of experimental designing and testing of prototypes of agricultural machines in the real-life conditions are of the great importance.…”
Section: Introductionmentioning
confidence: 99%